The association between blood groups, Rhesus factors, body mass index and obesity among pregnant women at Gadarif Maternity Hospital, Eastern Sudan - Amal O Bashir; Ahmed Ali Hassan; EL Bagir Mahdi; Gamal K Adam; Nadiah AlHabardi; Ishag Adam (BMC, 2023)
Abstract Background The existing evidence regarding the link between blood groups and obesity remains inconclusive, and there is a noticeable lack of data on the potential association between blood groups and obesity during pregnancy. Consequently, this study aimed to investigate the association between blood groups, body mass index (BMI), and obesity among pregnant women receiving care at Gadarif Maternity Hospital in eastern Sudan. Methods This cross-sectional study was conducted in eastern Sudan during the period from April to September 2022. A questionnaire was employed to gather sociodemographic information from pregnant women. BMI was computed based on weight and height. Blood groups determinations were made using the agglutination method which is commonly used in the study's region. Multinominal and multiple linear regression analyses were performed, and adjusted for covariates in the regression models. Results Eight hundred and thirty-three pregnant women were enrolled with a median (interquartile range, IQR) gestational age of 10.0 (9.3‒11.0) weeks. The median (IQR) BMI of the women was 26.3(24.2‒29.4) kg/m2. Of these women, 11(1.3%) were underweight, 268(32.2%) were of normal weight, 371(44.5%) were overweight, and 183(22.0%) were obese. One hundred eighty-three (22.0%) women had blood group A, 107 (12.8%) had blood group B, 56 (6.7%) had blood group AB, and 487(58.5%) had blood group O. While 798 (95.8%) of the women were Rhesus factor positive, only 35 (4.2%) were Rhesus factor negative. Multinominal regression showed that only urban residency (adjusted odds ratio, AOR = 2.46, 95% confidence interval, CI = 1.47‒4.13) was associated with overweight. Blood groups and Rhesus factors were not associated with overweight. Age (AOR = 1.06, 95% CI = 1.01‒1.11), urban residence (AOR = 2.46, 95%, CI = 1.47‒4.13), and blood group O (AOR = 1.60, 95%, CI = 1.06‒2.40), were associated with obesity. Rhesus factors were not associated with obesity. In the multiple linear regression, age (coefficient = 0.07, P = 0.028), gravidity (coefficient = 0.25, P = 0.014), urban residence (coefficient = 1.33, P = 0.001), and blood group O (coefficient = 0.68, P = 0.035) were associated with BMI. Conclusions Blood group O was associated with obesity and high BMI among pregnant women in eastern Sudan. Rhesus factors were not associated with obesity.